Buckling analysis of I-beams using finite element analysis - Ng, Gimson Jun Shun (Nanyang Technological University, 2020)
I-beams are steel structures that are widely used in the construction and civil engineering industry and are available in a variety of standard sizes. Due to its I-shaped section, it is able to efficiently bear both bending and shear loads in the plane of the web. However, as a result of its cross-section being an open section, it is inefficient in carrying torsion loads. This results in lateral torsional buckling being one of the failure modes for the I-beam. This study aims to conduct buckling analysis on a specific I-beam for different load cases and document the buckling load multiplier and buckling mode shapes. In addition, an algorithm would be developed to automate the buckling analysis for the I-beam as its length is varied from a short beam to a long beam, and the buckling load multiplier recorded. From the data collected, one could determine the buckling safety factor of the I-beam for a given length and applied load, such that static stress safety factor = 3. Furthermore, the results were compared to theoretical and semi-empirical formulas to determine the extent of deviation between methods. Lastly, the minimum web thickness of the chosen I-beam was obtained for different lengths of the I-beam through a similar automation of the buckling analysis, such that both static stress safety factor = buckling safety factor = 3.